Evaluación de alternativas para una ptap en la vereda El Floral, municipio de Melgar-Tolima. (2023)
This degree work contains the evaluation of alternatives for a Drinking Water Treatment Plant for the Vereda El Floral, in the municipality of Melgar, Tolima, evaluated by means of a matrix and an analytical method, in which three alternatives were established. Different, subjected to a weighting system based on the analysis of different criteria according to experts, where the highest weighting was the alternative chosen for the schematic design of the Drinking Water Treatment Plant (PTAP) for the village of El Floral.